(3CQHY cJH dHWdjehS aj GdbVGA Ydi OdGFd GdfLhes - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s
(3ChdgG (B:s
(3bGd HWdjehS ai GdcJGH GdChd ef cJHg gPg GdCQHYg SHYg hYTQhf HGHG gi GdCeQ GdeYJeO Ydjg ai GdbVGA s
(3BNQgG (B:s
(3BNQ GdcJGH GdQGHY CNJJe Hg cJGHi gPG Ydi CUd eG HdZg Ydei hJLQHJi hCMSf eGJgjC Hi Gdbhd ajg Ef TGA Gddg s
(3Gdajde ZjQ ehLhOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B7 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B123) s
Keywords: (3Gdadcs